Aposentadoria e trabalho: investigação sobre a (re)inserção do idoso no mercado de trabalho - Mori, Marcos Massanobu (2006)
The purpose of this study was to investigate the (re)insertion of the retired elder that Works and whit his/her dreams dan assure his/her consumer status that contributes to the decrease of his/her social rejection. In the developed countries, people over 40 years old have less job opportunities turning into victims of unemployment. Retirement to the represents discontinuity and a rupture with the activities developed before it, besides causing poverty. In this study, nine retired individuals were interviewed that declared their difficulties with the lower salary that they earn. Thus, they need to continue in the job market to help their family to survise. These individuals realize the injustice of the social welfare and know the problems found to stay active in the job market. It was possible to conclude that working gives pleasure to the retired elder, makes him feel useful and valued. It is observed that the elder remains working in order to maintain his/her needs. However, it is hoped that in the future he/she can dream of a world where oldness and expropriation of the right to work are history